Про деякі аспекти формування особистості майбутнього психолога як представника сучасної інтелігенції - Романовський, Олександр Георгійович (НТУ "ХПІ", 2012)
У статті розкрито поняття «інтелігентність», якості майбутнього психолога як представника інтелігенції. Визначено шляхи формування майбутнього психолога як представника інтелігенції. Розкрито конкретні дисципліни, що сприяють розвитку якостей інтелігента.

The article discloses the concept of «intelligence», the quality of the future psychologist as a representative of the intelligentsia. The ways of formation of the future psychologist as a representative of the intelligentsia. Identifies specific discipline, contributing to the development of the qualities of an intellectual.
About some aspects of the formation of the personality of the future psychologist as a representative of modern intellectuals
Keywords: підготовка професійна; підготовка фахівців; підхід людиноцентристський; гуманізація; духовність; якості професійні; культура комунікативна